The transformation of stage design in the 21st century Malaysian bangsawan / Muhammad Alhakeem Husain - Husain, Muhammad Alhakeem (2024)
Bangsawan is a traditional theatre form that consists of acting, singing, music, dancing, and has a strong influence from Wayang Parsi from India. It was brought to Penang, Malaysia in the 1870s and experienced a period of fame in the 1890s and began its downfall in the early 1940s. The Semarak Bangsawan program, launched in 2007, has allowed new Bangsawan groups to develop their own works. These groups have started incorporating contemporary and popular elements into their performances. For instance, many groups have replaced the traditional canvas Latar Tirai with light-emitting diodes (LED) to project their visual scene elements and technology has become an integral part of most Bangsawan performances, challenging traditional norms. This research aims to identify the transformation of stage design in 21 st-century Bangsawan performances in Malaysia. The focus of the study is to discuss the stage designs of Bangsawan Tengku Anum (2002) and Bangsawan Dendam Laksamana (2017). It is crucial to examine the 21st-century Bangsawan performances, where technology has been incorporated into theatrical productions. A qualitative research approach which involves historical research, content analysis and interviews. This research employs Pamela Howard's (2009) aspects of scenography as a primary tool for analysis which examines the elements of space, research, colors and composition aspects in the set designs. From this research, it reveals that LED and projectors have been utilized as substitutes for traditional canvas and painted backdrops in stage design in Bangsawan. The changes of traditional Latar Tirai gives a new method that can be usage on the Bangsawan performances. It provides an innovation in Bangsawan traditional theatre performance. Furthermore, this research highlights that the modifications of the set designs in the 21 st-century Bangsawan, do not change the conventional Bangsawan. It is because the performance's structure and other conventions remained, but has introduced new dimensions mainly to the set design. It is shown that the transformation of Latar Tirai in Bangsawan Tengku Anum and Bangsawan Dendam Laksamana are adapting to the current modem stage technologies and especially in competing with the contemporary theatre today. Therefore, the transformation of 21 st-century Bangsawan offers a new attractions to the urban audiences and also contributes to the preservation and conservation of dying traditional art form.